The Case of Bipolar Disorder Treated with Gelsemium (Advancements in Homeopathic Research, 2022)
Depression is one of the form of mood disorders characterized by predominant disturbances in mood. The prevalence of depressive disorder in general medical practice estimated 5 to 25 percent of clients in rural primary health care clinic 25% savior , 43% mild. We all have our ups and downs, but with bipolar disorder these peaks and valleys are more severe. The symptoms of bipolar disorder can hurt your job or school performance, damage your relationships, and disrupt your daily life. And although it’s treatable, many people don’t recognize the warning signs and get the help they need to feel well and do well. Since bipolar disorder tends to worsen without treatment, it’s important to learn what the symptoms look like. Recognizing the problem is the first step to feeling better and getting your life back on track.
Keywords: Bipolar; Mania; Mood; Episourse; Hypomania; Depression; Cyclophymia